Função de bactérias e fungos ruminais na degradação de forragens in vitro - Rösler, Dérick Cantarelli (2021)
The study was conducted to evaluate the interactive role of bacteria and fungi on the degradation of forages C3 and C4 in vitro. Dry and ground (1 mm) samples of Cynodon spp. (Tifton 85) and Lolium multiflorum Lam. (Azevém) were weighed (1.5 g) in triplicate in 160 mL flasks and incubated in vitro for 48 h in medium (50 mL buffer + 50 mL ruminal inoculum) containing or not antimicrobial substances. A mixture of penicillin, chloramphenicol and streptomycin (500 mg/L each) was used as an antibiotic and cycloheximide (50 mg/L) was used as antifungal. In vitro fermentations were carried out anaerobically in water-bath slow-stir system at 39 °C. The treatments were: antibiotic (F), antifungal (B), positive control (BF+, without antimicrobials) and negative control (BF-, with antimicrobials). Three replicate assays were performed for each forage and, in each assay the gas volume was measured at 3, 6, 9, 12, 24, 36 and 48 hours of incubation. For 24, 36 and 48 hours there was a three replicate of flasks of each treatment, which the solid residue had its DNA extracted. The DNA of bacteria and rumen fungi at each treatment and hour was quantified by Polymerase Chain Reaction real time (qPCR) analysis. The enzymatic activity of each treatment, at each time, was evaluated through incubation with xylan and subsequent analysis of reducing sugars by the Somogyi-Nelson method. Data of cumulative gas production in each flask in each assay was fitted to an one-pool logistic model which generated three kinetic parameters: total gas production (V, mL), rate of gas production (Kd, %/h) and lag time (L, hours). The data were analyzed using the GLM procedure of the SAS and the means compared using the T Student test, with a significance value of 5%. Ruminal bacteria had the greater role in the degradation of forages. For tifton 85, fungi and bacteria interacted synergistically and allowed greater degradation and bacterial adherence. There was poor degradation and adherence of fungi to azevém, and bacteria was the main responsible for the adhesion and degradation of this forage. Greater enzymatic activity was observed for tifton 85, compared to azevém. The interaction of bacteria and fungi tends to have greater enzymatic activity and there was no difference between isolated populations about the production of enzymes. The results of this study contribute to a better understanding of the activity of fungi in the rumen, as well as its interaction with the bacterial population on the degradation of forages